Stipulation in contract from Islamic and Malaysian legal perspectives - Abdul Manap, Norhoneydayatie; Laluddin, Hayatullah; Mohd Kusrin, Zuliza; Salleh, Ahmad Dahlan; Mat Zai, Mat Noor; Muhammad Husni, Ahmad; Nik Abdul Ghani, Nik Abdul Rahim; Omar, Anwar Fakhri (Canadian Center of Science and Education, 2013)
Generally, a subject of legal obligation is bound to perform his/her obligation regardless of whether the source of the obligation comes from the Lawgiver or is initiated by the subject of the law himself. Contract is a source of obligation which is initiated by a subject of legal obligation. Therefore, a person who makes a contract is responsible to the contract he concludes. Thus he is obliged to observe and perform his duty as agreed upon in the contract. In some cases, additional conditions or stipulations are included in the contract. Theses stipulations or conditions present a form of obligation that has to be complied with by contracting parties. The purpose of this study therefore, is to examine whether additional conditions can be added into the contract from the perspective of Islamic law and Malaysian law or otherwise. Thus, this study attempts to elaborate on the concept of stipulations its nature and types from Islamic and Malaysian laws points of view. The study also analyzes the similarities and differences of the concept of stipulations between both laws. The study uses comparative and analytical methods. The finding of the study shows that the term of stipulation and its types in Islamic law and Malaysian law are similar. Therefore, it is suggested that the contracting parties before making any stipulation to their contract to seek the advice of experts in order to make sure their contract is according with the law and is Shari’ah compliant.